Prognostic nutritional index as a predictor of cardiovascular and all-cause mortality in American adults with hypertension: results from the NHANES database - Tang, Jing; Yang, Long; Yang, Guan-Ying; Li, Yan-Hong; Zhu, You-Sen; Li, Hui; Gao, Xiao-Ming (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFew studies have examined the relationship between nutritional status, as assessed by the Prognostic Nutrition Index (PNI), and incident cardiovascular mortality and all-cause mortality, particularly in hypertensive patients. This study aimed to examine the association between PNI and cardiovascular mortality and all-cause mortality in Americans with hypertension.MethodsData from this retrospective cohort study were obtained from the National Health and Nutrition Examination (NHANES) 1999–2016. Using data of The NHANES Public-Use Linked Mortality Files to assess all-cause mortality (ACM) and cardiovascular mortality (CVM). After excluding participants younger than 18 years, without hypertension, and with missing follow-up data, a total of 18,189 cases were included in this study. Persons with hypertension were divided by PNI into 4 groups: Q1 (PNI < 49.0), Q2 (PNI: 49.0–52.5), Q3 (PNI: 52.5–55.5), and Q4 (PNI > 55.5). We used the Cox proportional hazard regression model to explore the predictive role of PNI on ACM and CVM in American adults with hypertension. Restricted cubic spline (RCS) curves to investigate the existence of a dose-response linear relationship between them.ResultDuring a median follow-up period of 89 months, a total of 1,444 (7.94%) cardiovascular deaths occurred and 5,171 (28.43%) all-cause deaths occurred. Multifactorial COX regression analysis showed all-cause mortality [hazard ratio (HR): 0.584, 95% CI: 0.523–0.652, p < 0.001] and cardiovascular mortality (HR: 0.435, 95% CI: 0.349–0.541, p < 0.001) associated with Q4 group risk of malnutrition in PNI compared to Q1 group. RCS curves showed a nonlinear relationship between PNI and all-cause mortality and cardiovascular mortality (both non-linear p < 0.001).ConclusionsLower PNI levels are associated with mortality in patients with hypertension. PNI may be a predictor of all-cause mortality and cardiovascular mortality risk in patients with hypertension.